Islamic Peace Education: Internalization of God’s Feminine Names to Santri in the Syukrillah Islamic Boarding School - R. Widya Setiabudi Sumadinata; Otong Sulaeman; Dina Yulianti (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2020)
Amid public concern about increasing radicalism and intolerance among Indonesianstudents, discussions on the importance of peaceful education came again to draw attention. Through a qualitative research, we found a method of peaceful education teaching that is intrinsic and based on local wisdom about the feminine attributes of God which can be internalized by students so that they have a culture of peace. Through this method, the Syukrillah Islamic Boarding School, Cipongkor, West Java, has taught a comprehensive understanding of religion, recognition of different opinions on religions, and feminine characteristics which are essential qualities desired in peaceful education. This article offers a new perspective of peaceful education by adopting a local wisdom concept that hopefully enriches the discussion of peaceful education.